Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 95242 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plantae", "HasGeospatialIssue is false", "Geometry POLYGON((-7.470703 58.631216,-2.8125 59.355596,1.494140 54.977613,2.197265 51.727028,0.351562 50.007739,-5.976562 49.496674,-5.800781 51.890053,-5.097656 53.696706,-5.361328 55.128649,-8.173828 56.992882,-7.470703 58.631216))", "BasisOfRecord is Specimen" ] } The dataset includes 95242 records from 68 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001162-150216165555722/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences